2007
DOI: 10.1111/j.1365-2966.2006.11234.x
|View full text |Cite
|
Sign up to set email alerts
|

Helioseismic analysis of the solar flare-induced sunquake of 2005 January 15

Abstract: We report the discovery of one of the most powerful sunquakes detected to date, produced by an X1.2‐class solar flare in active region AR10720 on 2005 January 15. We used helioseismic holography to image the source of seismic waves emitted into the solar interior from the site of the flare. Acoustic egression power maps at 3 and 6 mHz with a 2‐mHz bandpass reveal a compact acoustic source strongly correlated with impulsive hard X‐ray and visible‐continuum emission along the penumbral neutral line separating th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
67
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(75 citation statements)
references
References 24 publications
(46 reference statements)
7
67
0
Order By: Relevance
“…This is most likely due to several factors such as use of Model C as opposed to VAL, different pupil dimensions and different integration kernels (we use larger areas around 37 and 33 Mm 2 for Sources 1 and 2 correspondingly, as opposed to 12 Mm 2 (Alvarado-Gómez, Buitrago-Casas, Martínez-Oliveros et al (2012), C. Lindsey, private communication, 2012). The estimate for Source 1 puts it amongst the most powerful sunquakes associated with X-class flares (Moradi, Donea, Lindsey et al, 2007;Besliu-Ionescu, Donea, Cally et al, 2005). We note, however, that Besliu-Ionescu, Donea, Cally et al (2006) reports an even stronger seismic event for the M7.8 flare on 2 December 2005.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…This is most likely due to several factors such as use of Model C as opposed to VAL, different pupil dimensions and different integration kernels (we use larger areas around 37 and 33 Mm 2 for Sources 1 and 2 correspondingly, as opposed to 12 Mm 2 (Alvarado-Gómez, Buitrago-Casas, Martínez-Oliveros et al (2012), C. Lindsey, private communication, 2012). The estimate for Source 1 puts it amongst the most powerful sunquakes associated with X-class flares (Moradi, Donea, Lindsey et al, 2007;Besliu-Ionescu, Donea, Cally et al, 2005). We note, however, that Besliu-Ionescu, Donea, Cally et al (2006) reports an even stronger seismic event for the M7.8 flare on 2 December 2005.…”
Section: Discussionmentioning
confidence: 84%
“…Considerable anisotropy in the acoustic amplitude of the ripples from the vantage of the sources has been observed for most quakes (Kosovichev, 2006;Moradi, Donea, Lindsey et al, 2007;Donea, 2011). In fact, Donea (2011) suggests that the maximum amplitude of the ripples emanating from a moving source is generally along the axis of the source, displaced from the source location in the direction of the motion.…”
Section: Discussionmentioning
confidence: 99%
“…As far as we are aware, so far for every quake detected with TD ridges there was associated acoustic emission detected via egression analysis (1996 July 9, Kosovichev & Zharkova 1998;2001March 10, Martínez-Oliveros & Donea 20092003October 28, Zharkova & Zharkov 2007Donea et al 1999;January 15, Martínez-Oliveros et al 2008bMoradi et al 2007). Moreover, it can be argued that this might generally be the case, since the egression computation uses virtually the same data and should revert the anomalous wave-field fluctuations seen as a TD ridge to a source.…”
Section: Statistical Significance Of Seismic Signaturesmentioning
confidence: 99%
“…They produce a characteristic signature tens of thousands of kilometers from the origin where they refract back to the solar surface over the succeeding hour. Computational seismic holography applied to these surface signatures shows a relatively compact source distribution (Donea, Braun & Lindsey 1999;Donea et al 2006;Moradi et al 2007;Martínez-Oliveros et al 2007) closely associated with both hard X-ray and white-light emission (Donea & Lindsey 2005) Kosovichev & Zharkova (1998) suggested that the initial source of flare acoustic transients was impulsive thick-target heating of the chromosphere by high energy particles beams (Zharkova & Kobylinskii 1993). This suggestion was strongly reinforced by Donea & Lindsey (2005), who found that the acoustic sources were closely co-spatial with hard X-ray emission observed by RHESSI a result confirmed also by Kosovichev (2006a,b,c) and Donea et al (2006).…”
Section: Introductionmentioning
confidence: 99%